(untitled) (Philological Studies, 2019)
In the novels Filio Isn’t Home (Filio ni doma) and The Eighth Commissioner (Osmi poverjenik) we can observe characteristics of anti-utopia, dystopia and utopia. As the setting in both works is an island we speak of spatial escapism. To understand the novels set on these islands it is crucial to understand sexuality, male-female relationships, gender roles, authority and hierarchical organisational structure.